Visit Characteristics Associated With Pediatric Dental Appointment No-Shows in an Academic Dental Setting - Rubelisa C. G. de Oliveira; Hassan Khalid; Zhaoqi Zhang; Saptarshi Chakraborty; Daniela Benzano; Jessica S. Kruger; Susan C. McKernan (International Journal of Dentistry)
Conclusions: Adolescents are the group at most risk of no-show. Future studies should explore strategies to better understand the barriers related to this lifespan as well as implement interventions that facilitate scheduling as well as prevent no-shows.